THE ROLE OF PEDAGOGICAL RHETORIC IN DEVELOPING SPEECH LITERACY COMPETENCE (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the role of pedagogical rhetoric in the formation of speech literacy among future teachers. It analyzes the theoretical foundations of rhetoric, its connection with communicative competence, and its importance in professional pedagogical communication. The article emphasizes that speech literacy includes not only linguistic correctness, but also logical organization, persuasive argumentation, ethical communication, audience awareness, and reflective self-assessment. Special attention is given to rhetorical methods such as explanation, questioning, dialogue, feedback, and argumentation as effective tools for developing future teachers’ professional speech.
Keywords: speech literacy, pedagogical rhetoric, future teachers, communicative competence, argumentation, professional speech.